2021
DOI: 10.3390/ijms22062900
|View full text |Cite
|
Sign up to set email alerts
|

One Heat Shock Transcription Factor Confers High Thermal Tolerance in Clematis Plants

Abstract: Clematis plants play an important role in botanical gardens. Heat stress can destroy the activity, state and conformation of plant proteins, and its regulatory pathway has been well characterized in Arabidopsis and some crop plants. However, the heat resistance response mechanism in horticultural plants including Clematis has rarely been reported. Here, we identified a heat-tolerant clematis species, Clematis vitalba. The relative water loss and electrolytic leakage were significantly lower under heat treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…6 b and 10 ), suggesting that HSFA2 may play an important role in the heat response of C. crassifolia . CvHSF30-2 was a transcription factor induced by heat stress in Clematis vitalba , which improved the heat tolerance of C. vitalba by increasing the expression of HSPs [ 73 ]. Upregulation of HSF30 ( c194517_g1 ) was also observed in C. lanuginosa and C. crassifolia (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…6 b and 10 ), suggesting that HSFA2 may play an important role in the heat response of C. crassifolia . CvHSF30-2 was a transcription factor induced by heat stress in Clematis vitalba , which improved the heat tolerance of C. vitalba by increasing the expression of HSPs [ 73 ]. Upregulation of HSF30 ( c194517_g1 ) was also observed in C. lanuginosa and C. crassifolia (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Diaminobenzidine (DAB) and nitrotetrazolium blue (NBT) staining: take control plants or leaves of irradiated plants as samples, add DAB or NBT staining solution (both liquids were not over the samples), heat the water bath at 100 °C for 5 min, leave the staining solution for 16 h in a place protected from light, pour out the staining solution, wash the samples with distilled water 2~3 times, add anhydrous ethanol, heat the water bath for 5 min, pour out the ethanol, repeat until decolorization, add 40% volume fraction of glycerol solution, leave the solution in a place protected from light for 2 h, pour out the glycerol solution, and observe [ 48 ].…”
Section: Methodsmentioning
confidence: 99%
“…Maize (Zea mays) mitochondrial sHsps showed protection against NADH and improved mitochondrial electron b transport during salt stress [8]. The accumulation of SlHSP21.5A can increase the tolerance of rice (Oryza sativa) to salt stress [9]; overexpression of CaHSP25.9 can enhance pepper (Piper nigrum) tolerance to heat, salt and drought stress; CaHSP16.4 is related to pepper (Piper nigrum) heat and drought tolerance [10,11]; overexpression of KSlHSP21.5A can enhance tomato (Solanum lycopersicum) tolerance to heat stress [12]; the expression of CvHSF30-2 can improve the heat resistance of clematis (Clematis tibetana) [13]. More and more studies have shown that there is a strong correlation between the accumulation of sHsps and the stress tolerance of plants.…”
Section: Introductionmentioning
confidence: 99%